2015
DOI: 10.1108/apjml-08-2014-0124
|View full text |Cite
|
Sign up to set email alerts
|

Category captain arrangements in grocery retail marketing

Abstract: Purpose – The purpose of this paper is to examine shelf management practices of grocery retail chains and their category captains (CCs) in the marketing of consumer packaged goods. Design/methodology/approach – This is a qualitative, exploratory study that is set in a duopoly retail environment in the Asia-Pacific region. The study employed 18 in-depth interviews with executives and managers of two umbrella retail organisations and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Thus, assortment decisions determine a retailer’s market position and image (e.g. Chimhundu et al , 2015; Mantrala et al , 2009), heavily influence a retailer’s sales and profits and are crucial for long-term success (Bahng and Kincade, 2014; Bauer et al , 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, assortment decisions determine a retailer’s market position and image (e.g. Chimhundu et al , 2015; Mantrala et al , 2009), heavily influence a retailer’s sales and profits and are crucial for long-term success (Bahng and Kincade, 2014; Bauer et al , 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Fyfe and Millar, 2012). In addition, while in the grocery retail environments, retailers overall wield more power over manufacturers (Chimhundu et al , 2015), manufacturer brands remain important for store traffic (Ngobo, 2011). These seemingly conflicting consequences of manufacturer brand erosion demand formal investigation.…”
Section: Introductionmentioning
confidence: 99%
“…This was also likely to apply to private label suppliers who had a deeper understanding of the own-brand market. They could therefore focus on their niche and carry out the correct market analysis and product development to make informed recommendations (Chimhundu, Kong and Gururajan, 2015). The research found that category captains needed to continuously invest money into the relationship to maintain captaincy, whereas non -captains did not.…”
Section: S7 (L B)mentioning
confidence: 99%
“…Non-captains therefore gained the overall profit growth without investing the capital themselves. However, if a smaller supplier did want to obtain captaincy, previous research has implied that this would be more difficult, due to the size of the business (Hamister and Fortsch, 2016;Chimhundu, Kong and Gururajan, 2015). Previous research has shown that the larger suppliers tended to gain captaincy, but if the smaller ones or private label ones did, this was due to the operant resources provided, for example, due to their ability to analyse data and make intellectual recommendations that surpassed those of their competitors (Harrison-Walker, 2001).…”
Section: S7 (L B)mentioning
confidence: 99%
See 1 more Smart Citation